Meta Sintesis: Penggunaan E-Portofolio sebagai Asesmen Alternatif dalam Pembelajaran Biologi - Ma’fud, Sukhrul; Abidin, Zaenal (EduInovasi: Journal of Basic Educational Studies, 2025)
The digital transformation in education has driven a paradigm shift in assessment, from traditional forms to technology-based alternatives such as e-portfolios. The purpose of this study is to analyze the implementation patterns of e-portfolios in biology learning, evaluate their impact on student competency development, and identify implementation barriers. The research method used a meta-synthesis approach to English-language articles published between 2020 and 2025 from the Google Scholar database. A search using the combination of keywords "e-portfolio," "assessment," and "biology learning" yielded 200 articles, which were then systematically selected to obtain eight articles that met the criteria for meta-synthesis. Results: The results indicate that e-portfolios are implemented using various platforms such as Google Sites, WordPress, and Google Classroom, at high school and university levels, with varying biology materials. In general, e-portfolios have been shown to improve digital literacy (100%), creativity (75%), science communication (75%), and critical thinking (62.5%). However, several aspects, such as learning independence (25%) and metacognition (37.5%), are still not optimal. The main obstacles identified include difficulty adapting to technology (62.5%) and unstable internet connections (50%). These findings indicate that although e-portfolios have great potential as an alternative assessment in biology learning, their success is highly dependent on technological readiness, user digital competence, and institutional support. This study makes an important contribution to understanding the role of e-portfolios as an innovative assessment tool and identifying areas for improvement for more effective implementation in the future.